Lexico-Syntactic in Free Indirect Speech Connectors and the Problem of Marking the Point of View of the Narrator and Character - V. Krasnova, Evgenia; V. Kotelnikova, Inna; E. Marchenko, Svetlana; A. Topolskaya, Irina; P. Avedova, Renata (International Journal of Psychosocial Rehabilitation, 2020)
The present research aims to determine the features of lexico-syntactic connectors in free indirect speech and to establish the specificity of representing the point of view of the narrator and character through the considered pragmatic markers of free indirect speech. The relevance of the study lies in the development of ideas about the formation (in the cognitive consciousness of the author and the reader) of counterpoint characters voices that form the basis of polyphonic language thinking. The research results complement the currently relevant linguistic concepts of artistic discourse. The purpose and objectives of the study are realized by such research methods as: descriptive-analytical method based on contextual analysis, conceptual analysis, and comparative method. The analysis of 3375 contexts established that the lexico-syntactic connectors can act as an effective means of creating linear continuity of free indirect speech. It is proved that sentences containing lexico-syntactic connectors receive the same interpretation in the text as in the previous context space. It is established that the lexico-syntactic connectors connect not only the preceding and the subsequent discourse segments but also different cognitive states of the character. It is argued that the connectors are triggers to shift from one point of view to another, contributing to the harmonization of different points of view. In conclusion, it is determined that the manipulation of the connecting means in the translation process can significantly affect the reader’s perception of the points of view of the characters and the author’s narration.